Sex differences in type 2 diabetes: focus on disease course and outcomes - Arnetz L (Dove Medical Press, 2014)
Lisa Arnetz,1,2 Neda Rajamand Ekberg,1,2 Michael Alvarsson1,2 1Department of Molecular Medicine and Surgery, Karolinska Institutet, 2Department of Endocrinology, Metabolism and Diabetes, Stockholm, Sweden Background: Women with type 2 diabetes (T2D) are less likely to reach the goals for hemoglobin A1c compared with men, and have higher all-cause mortality. The risk of cardiovascular disease is elevated among both men and women with T2D, however, the risk has declined among men over recent years while it remains stationary in women. Reasons for these sex differences remain unclear, and guidelines for diabetes treatment do not differentiate between sexes. Possible causes for varying outcome include differences in physiology, treatment response, and psychological factors. This review briefly outlines sex differences in hormonal pathophysiology, and thereafter summarizes the literature to date on sex differences in disease course and outcome. Methods: Systematic searches were performed on PubMed using “sex”, “gender”, and various glucose-lowering therapies as keywords. Earlier reviews are summarized and results from individual studies are reported. Reference lists from studies were used to augment the search. Results: There is an increased risk of missing the diagnosis of T2D when screening women with only fasting plasma glucose instead of with an oral glucose tolerance test. The impact of various risk factors for complications may differ by sex. Efficacy and side effects of some glucose-lowering drugs differ between men and women. Men with T2D appear to suffer more microvascular complications, while women have higher morbidity and mortality in cardiovascular disease and also fare worse psychologically. Conclusion: Few studies to date have focused on sex differences in T2D. Several questions demand further study, such as whether risk factors and treatment guidelines should be sex-specific. There is a need for clinical trials designed specifically to evaluate sex differences in efficacy and outcome of the available treatments. Keywords: type 2 diabetes, gender, sex, complications, cardiovascular disease, treatment